Electrode active material composition, and electrode and secondary battery including the same

By using polyhydroxyalkanoate (PHA) as the adhesive in the electrode of a lithium secondary battery, the electrode performance problems caused by excessive or insufficient use of adhesives in the prior art are solved, and the battery performance with high capacity, long life and high output is achieved.

CN119631198APending Publication Date: 2025-03-14CJ CHEILJEDANG CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380052682.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-20
Filing Date
2023-07-19
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the electrodes of existing lithium secondary batteries, excessive adhesive will lead to reduced electrode capacity and conductivity, while a small amount of adhesive may lead to insufficient adhesive strength, increasing the risk of electrode defect rate and degradation of output performance.

Method used

Using polyhydroxyalkanoate (PHA) as the adhesive, PHA has excellent adhesive strength, oxidation resistance and electrochemical stability, and can achieve high capacity, long life and high output of the secondary battery when a small amount of adhesive is used.

Benefits of technology

By using PHA as the adhesive, the electrode active material composition can significantly improve the bond strength and electrochemical properties, extend the life of the secondary battery, and maintain high capacity and low resistance during repeated charge and discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119631198A_ABST
    Figure CN119631198A_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode active material composition, and an electrode and a secondary battery comprising the same, the composition comprising an electrode active material, a binder and a conductive material, in which the binder contains a polyhydroxyalkanoate (PHA). According to the electrode active material composition, polyhydroxyalkanoate (PHA) is used as an adhesive, so that the adhesion between the active materials and between the active materials and an electrode current collector can be further improved; having excellent oxidation resistance and being electrochemically stable; the present invention relates to a binder for a secondary battery, and can achieve a long life, high capacity and high power output of the secondary battery even if a small amount of the binder is used, thereby making it possible not only to be used in a battery cell used as a power source for a small device, but also to be used in a unit battery of a medium and large battery module including a plurality of battery cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrode active material composition, and an electrode and a secondary battery including the same. Background Art

[0002] With the development of technology and the increase in demand for various means of transportation (such as electric vehicles, electric motorcycles, electric pedals, electric scooters, electric wheelchairs and electric bicycles, etc.) and mobile devices, the demand for secondary batteries as energy sources has increased rapidly. Among such secondary batteries, lithium secondary batteries have been commercialized to be widely used because they exhibit high energy density and working potential, long cycle life and low self-discharge rate.

[0003] The electrode of the lithium secondary battery is manufactured by mixing an electrode active material, a binder and a conductive material to prepare an active material composition, applying it to the surface of an electrode current collector, and drying to form a composite material layer.

[0004] In the above electrodes, the binder is used to ensure the bonding strength or the bonding strength between the active materials or between the active materials and the electrode current collector, and an excess amount of the binder is required to enhance the bonding strength between the electrode current collector and the active materials.

[0005] However, excessive amounts of binder may lead to problems such as reduced electrode capacity and reduced conductivity. On the other hand, a small amount of binder may reduce bonding strength, and insufficient bonding strength may cause electrode delamination during processes such as electrode drying and pressing, which may increase the electrode defect rate. In addition, electrodes with low bonding strength may delaminate due to external impact. Such electrode delamination may increase the contact resistance between the electrode material and the current collector, which may lead to a decrease in electrode output performance.

[0006] Meanwhile, examples of currently commercialized adhesives include polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC). However, it is necessary to develop an adhesive that can replace the above adhesives, can be easily purchased, is environmentally friendly, and can achieve equivalent or better effects in terms of life characteristics, output characteristics and capacity characteristics of secondary batteries.

[0007] [Prior art literature]

[0008] [Patent Document]

[0009] (Patent Document 1) Korean Patent No. 10-2071585 Summary of the invention

[0010] Technical issues

[0011] An object of the present disclosure is to provide an electrode active material composition, which contains polyhydroxyalkanoate (PHA) (environmentally friendly) as a binder, which provides excellent bonding strength between active materials and between active materials and electrode current collectors, enhances oxidation resistance and electrochemical stability, and can achieve high capacity and high output and long life characteristics of secondary batteries even with a small amount of binder, and has flame retardancy, does not spread combustion and does not produce harmful substances when polyhydroxyalkanoate (PHA) is incinerated.

[0012] Another object of the present disclosure is to provide an electrode and a secondary battery, each including the electrode active material composition having the above-mentioned characteristics.

[0013] Solution to the problem

[0014] According to an embodiment of the present disclosure, there is provided an electrode active material composition including an electrode active material, a binder, and a conductive material, wherein the binder includes polyhydroxyalkanoate (PHA).

[0015] According to another embodiment, the polyhydroxyalkanoate (PHA) may have a glass transition temperature (Tg) of -45°C to 80°C and a melt index (MI) of 0.1 g / 10 min to 500 g / 10 min, the melt index being measured at a temperature of 165°C and a load of 5.0 kg according to ASTM D1238.

[0016] According to another embodiment, the polyhydroxyalkanoate (PHA) may include at least one monomer selected from the group consisting of 4-hydroxybutyrate (4-HB), 3-hydroxybutyrate (3-HB), 3-hydroxypropionate (3-HP), 3-hydroxyvalerate (3-HV), 3-hydroxyhexanoate (3-HH), 4-hydroxyvalerate (4-HV), 5-hydroxyvalerate (5-HV) and 6-hydroxyhexanoate (6-HH).

[0017] According to another embodiment, the polyhydroxyalkanoate (PHA) may include a PHA homopolymer composed of 4-hydroxybutyrate (4-HB) monomers.

[0018] According to another embodiment, the polyhydroxyalkanoate (PHA) may include a PHA copolymer including a 4-hydroxybutyrate (4-HB) monomer, wherein the amount of the 4-hydroxybutyrate (4-HB) monomer may be 1 mol % to 99 mol % of the total moles of monomers used in the PHA copolymer.

[0019] According to another embodiment, the binder may be used in an amount of 0.1 wt % to 20 wt % based on the total weight of the electrode active material composition.

[0020] According to another embodiment, the weight ratio of the electrode active material, the binder and the conductive material may be (4.0 to 9.8):(0.1 to 3.0):(0.1 to 3.0).

[0021] According to another embodiment, the electrode active material may be a negative electrode active material.

[0022] According to another embodiment, the negative electrode active material may include at least one selected from the group consisting of: carbon-based negative electrode active materials, silicon-based negative electrode active materials, lithium metal and lithium alloys; and the conductive material may include at least one selected from the group consisting of: graphite, carbon black, conductive fibers, conductive tubes, metal powders, conductive whiskers and conductive metal oxides.

[0023] According to another embodiment of the present disclosure, there is provided an electrode including an electrode active material, a binder, and a conductive material, wherein the binder includes polyhydroxyalkanoate (PHA).

[0024] According to another embodiment of the present disclosure, provided is a secondary battery including a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte, wherein at least one of the negative electrode and the positive electrode includes a binder including polyhydroxyalkanoate (PHA).

[0025] According to another embodiment, when the secondary battery is charged at a constant current of 0.05C until the voltage reaches 3V and then discharged at a constant current of 0.05C until the voltage reaches 0.01V, the coulombic efficiency represented by the following equation 1 may be 93% or more, and the specific capacity measured after repeating the above charging and discharging twice may be 280mAhg -1 or higher:

[0026] [Equation 1]

[0027] Coulombic efficiency (%) = discharge capacity / charge capacity × 100.

[0028] Beneficial effects of the present invention

[0029] The electrode active material composition according to the embodiment of the present disclosure includes polyhydroxyalkanoate (PHA) as a binder. As a result, the bonding strength between the active materials and between the active materials and the electrode current collector can be further enhanced, excellent oxidation resistance and electrochemical stability are achieved, and even with a small amount of binder, the long life characteristics, high capacity and high output of the secondary battery can be achieved.

[0030] In addition, the secondary battery according to the embodiment of the present disclosure includes an electrode active material composition having the above-mentioned characteristics. As a result, electrochemical performance, such as coulombic efficiency and capacity characteristics, is further enhanced, whereby the composition can be used not only in a battery cell used as a power source for a small device, but also in a unit cell of a medium to large battery module containing a plurality of battery cells.

[0031] Specifically, the present disclosure has technical significance because polyhydroxyalkanoate (PHA) is used as a binder, polyhydroxyalkanoate can replace conventional binders (such as polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC)), which can be easily purchased, can achieve equivalent or better effects in terms of the physical properties of secondary batteries, and due to the use of PHA, has flame retardant properties that do not spread combustion and do not produce harmful substances when incinerated. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 are photographs showing the results of measuring the solubility of PVdF used in Comparative Example 1 and PHA used in Example 1 in the electrolyte.

[0033] Figure 2 (a) shows the voltage-current curves of the electrodes of Comparative Example 1 and Example 1. Figure 2 (b) shows the voltage-current curves of the polyvinylidene fluoride (PVdF) binder used in Comparative Example 1 and the PHA (3-HB-co-4-HB, aPHA) binder used in Example 1.

[0034] Figure 3 is a graph showing the results of measuring the specific capacity of the secondary batteries of Example 1, Example 2, and Comparative Example 1.

[0035] Figure 4 : is a graph showing the results of measuring the specific capacity and coulombic efficiency of the secondary battery of Example 1 according to the number of cycles.

[0036] Figure 5 : is a graph showing the results of measuring the specific capacity and coulombic efficiency of the secondary battery of Comparative Example 1 according to the number of cycles.

[0037] Figure 6 is a graph showing the results of measuring the impedance of the secondary batteries of Example 1 and Comparative Example 1 in the first cycle.

[0038] Figure 7 is a graph showing the results of measuring the impedance of the secondary batteries of Example 1 and Comparative Example 1 in the 10th cycle.

[0039] Figure 8: is a graph showing the results of measuring the specific capacity and coulombic efficiency of the secondary battery of Example 2 according to the number of cycles.

[0040] Best Mode for Carrying Out the Invention

[0041] Hereinafter, the present disclosure will be described in detail with reference to the embodiments. The embodiments are not limited to those described below. Instead, they can be modified into various forms as long as the gist of the present disclosure is not changed.

[0042] Throughout the specification, when a part is referred to as “comprising” an element, it should be understood that it may include other elements, rather than excluding other elements, unless specifically stated otherwise.

[0043] In the present specification, when mentioning that an element is formed “on” or “under” another element, this not only means that one element is directly formed “on” or “under” another element, but also means that one element is indirectly formed on or under another element with one or more other elements interposed therebetween.

[0044] Throughout the specification, the terms first, second, etc. are used to describe different components. However, the components should not be limited by the terms. These terms are only used for the purpose of distinguishing one component from another. In addition, unless otherwise specified, all numbers used herein to represent the physical properties, dimensions, etc. of the elements should be understood to be modified by the term "about".

[0045] [Electrode Active Material Composition]

[0046] An electrode active material composition according to an embodiment of the present disclosure includes an electrode active material, a binder, and a conductive material, wherein the binder includes polyhydroxyalkanoate (PHA).

[0047] Generally, the binder in a secondary battery is a material that physically stabilizes the electrodes of the secondary battery. It not only acts as a type of adhesive to fix the electrode active material and the conductive material to the current collector, but also prevents the bond between the electrode active material and the conductive material from becoming loose when the secondary battery is repeatedly charged and discharged. Therefore, the adhesive properties, solubility in solvents, structural stability, and oxidation resistance of the binder may have a significant impact on the performance of the secondary battery.

[0048] Polyhydroxyalkanoate (PHA) is used as a binder in the present disclosure. As a result, polyhydroxyalkanoate has significant advantages because it can further enhance the bonding strength between active materials and between active materials and electrode current collectors, has excellent oxidation resistance and electrochemical stability, can achieve long life characteristics, high capacity and high output of secondary batteries even with a small amount of binder, and has flame retardancy, does not spread combustion and does not produce harmful substances when polyhydroxyalkanoate (PHA) is incinerated.

[0049] Hereinafter, each component of the electrode active material composition of the present disclosure will be described in detail.

[0050] Adhesives

[0051] The electrode active material composition according to an embodiment of the present disclosure includes a binder which is a polymer additive that can physically stabilize an electrode, wherein the binder may include polyhydroxyalkanoate (hereinafter referred to as PHA).

[0052] PHA is a material that can replace conventional binders, can be easily purchased, and can achieve equivalent or better results in terms of the performance of secondary batteries; therefore, PHA can be advantageously used in secondary batteries.

[0053] Specifically, PHA has excellent bonding strength, is electrochemically stable, and has excellent oxidation resistance, making it very suitable as a binder for secondary batteries. In addition, when the binder is used in a secondary battery, it can maintain structural stability even after long-term cycling, thereby achieving high capacity and long life characteristics, and it can maintain high capacity cycling for a long time due to low resistance even after repeated charge and discharge cycles, thereby improving the performance of the secondary battery.

[0054] The physical properties of PHA are similar to those of conventional petroleum-derived synthetic polymers, such as polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), polybutylene succinate terephthalate (PBST), and polybutylene succinate adipate (PBSA), are fully biodegradable, and have excellent biocompatibility.

[0055] Specifically, PHA is a natural thermoplastic polyester polymer that accumulates in microbial cells. Since it is a biodegradable material, it can be composted and eventually decomposed into carbon dioxide, water, and organic waste without generating toxic waste. In particular, since PHA resin is biodegradable in soil and oceans, it has environmentally friendly characteristics.

[0056] The PHA may be a PHA homopolymer composed of one monomer or a PHA copolymer comprising two or more different monomers. Alternatively, the PHA may include a PHA homopolymer and a PHA copolymer.

[0057] When the PHA is a copolymer, it can be, for example, a copolymeric PHA comprising two or more different repeating units, wherein the different monomers are randomly distributed in the polymer chain.

[0058] Examples of monomers that may be included in PHA include 2-hydroxybutyrate, lactic acid, glycolic acid, 3-hydroxybutyrate (hereinafter referred to as 3-HB), 3-hydroxypropionate (hereinafter referred to as 3-HP), 3-hydroxyvalerate (hereinafter referred to as 3-HV), 3-hydroxyhexanoate (hereinafter referred to as 3-HH), 3-hydroxyheptanoate (hereinafter referred to as 3-HHep), 3-hydroxyoctanoate (hereinafter referred to as 3-HO), 3-hydroxynonanoate (hereinafter referred to as 3-HN), 3-hydroxydecanoate (hereinafter referred to as 3-HD), 3-hydroxydodecanoate (hereinafter referred to as 3-HDd), 4-hydroxybutyrate (hereinafter referred to as 4-HB), 4-hydroxyvalerate (hereinafter referred to as 4-HV), 5-hydroxyvalerate (hereinafter referred to as 5-HV), and 6-hydroxyhexanoate (hereinafter referred to as 6-HH). PHA may contain one or more monomers selected from the above.

[0059] Specifically, the polyhydroxyalkanoate (PHA) may include at least one monomer selected from the group consisting of 4-hydroxybutyrate (4-HB), 3-hydroxybutyrate (3-HB), 3-hydroxypropionate (3-HP), 3-hydroxyvalerate (3-HV), 3-hydroxyhexanoate (3-HH), 4-hydroxyvalerate (4-HV), 5-hydroxyvalerate (5-HV) and 6-hydroxyhexanoate (6-HH).

[0060] More specifically, the PHA may include a PHA homopolymer consisting of a monomer selected from the group consisting of 4-HB, 3-HB, 3-HP, 3-HV, 3-HH, 4-HV, 5-HV and 6-HH; or a PHA copolymer comprising one or more monomers selected from the group consisting of 4-HB, 3-HB, 3-HP, 3-HV, 3-HH, 4-HV, 5-HV and 6-HH.

[0061] Specifically, the PHA may be a PHA homopolymer composed of a monomer selected from the group consisting of 4-HB and 3-HB; or a PHA copolymer including one or more monomers selected from the group consisting of 4-HB and 3-HB.

[0062] More specifically, the PHA may comprise a 4-HB monomer.

[0063] The PHA may comprise a PHA homopolymer composed of 4-HB monomers.

[0064] Furthermore, the PHA may be a PHA copolymer comprising a 4-HB monomer.

[0065] For example, the PHA may be a PHA copolymer including a 4-HB monomer and further including one monomer different from the 4-HB monomer, or further including two, three, four, five, six or more monomers different from each other.

[0066] According to an embodiment of the present disclosure, PHA may include a 4-HB monomer; and one or more monomers selected from the group consisting of 3-HB, 3-HP, 3-HV, 3-HH, 4-HV, 5-HV and 6-HH. More specifically, PHA may include a PHA copolymer containing a 3-HB monomer and a 4-HB monomer.

[0067] For example, the PHA may be poly-3-hydroxybutyrate-co-4-hydroxybutyrate (hereinafter referred to as 3HB-co-4HB).

[0068] In addition, PHA may contain isomers. For example, PHA may contain structural isomers, enantiomers or geometric isomers. Specifically, PHA may contain structural isomers.

[0069] According to an embodiment of the present disclosure, in order to be suitable for use as a binder for a secondary battery and to achieve the desired performance of an electrode and a secondary battery in the present disclosure, specifically, a PHA containing a 4-HB monomer may be used. In this case, it may be important to control the content ratio of the 4-HB monomer.

[0070] For example, the polyhydroxyalkanoate (PHA) may include a PHA copolymer containing a 4-hydroxybutyrate (4-HB) monomer, wherein the amount of the 4-hydroxybutyrate (4-HB) monomer used may be 1 mol % to 99 mol % of the total moles of monomers used in the PHA copolymer.

[0071] Specifically, the PHA may include a PHA copolymer containing a 3-HB monomer and a 4-HB monomer, wherein the PHA copolymer may include 1 mol% to 99 mol% of the 4-hydroxybutyrate (4-HB) monomer based on the total moles of the 3-hydroxybutyrate (3-HB) monomer and the 4-hydroxybutyrate (4-HB) monomer. For example, the PHA copolymer may include 1 mol% or more, 2 mol% or more, 3 mol% or more, 5 mol% or more, or 10 mol% or more, and 99 mol% or less, 95 mol% or less, 90 mol% or less, 85 mol% or less, 80 mol% or less, 75 mol% or less, 70 mol% or less, 65 mol% or less, or 60 mol% or less of the 4-hydroxybutyrate (4-HB) monomer based on the total moles of the 3-hydroxybutyrate (3-HB) monomer and the 4-hydroxybutyrate (4-HB) monomer. Specifically, the PHA copolymer may contain 1 mol% to 99 mol%, 1 mol% to 95 mol%, 1 mol% to 90 mol%, 1 mol% to 89 mol%, 1 mol% to 85 mol%, 1 mol% to 80 mol%, 1 mol% to 79 mol%, 1 mol% to 75 mol%, 1 mol% to 70 mol%, 1 mol% to 65 mol%, 1 mol% to 60 mol%, 1 mol% to 55 mol%, 1 mol% to 50 mol%, 2 mol% to 55 mol%, 3 mol% to 55 mol%, 3 mol% to 50 mol%, 5 mol% to 55 mol%, 5 mol% to 50 mol%, 10 mol% to 55 mol%, 10 mol% to 50 mol%, 15 ... % to 60 mol%, 15 mol% to 55 mol%, 15 mol% to 50 mol%, 20 mol% to 60 mol%, 20 mol% to 55 mol%, 20 mol% to 50 mol%, 25 mol% to 60 mol%, 25 mol% to 55 mol%, 25 mol% to 50 mol%, 25 mol% to 45 mol%, 25 mol% to 40 mol%, 30 mol% to 60 mol%, 30 mol% to 55 mol%, 30 mol% to 50 mol%, 30 mol% to 45 mol%, 30 mol% to 40 mol%, 35 mol% to 60 mol%, 35 mol% to 55 mol%, 35 mol% to 50 mol%, 40 mol% to 60 mol%, 40 mol% to 55 mol%, or 45 mol% to 55 mol%.

[0072] According to another embodiment, the PHA copolymer may contain 4-HB monomer in an amount of 1 mol% to 99 mol% based on the total moles of monomers used in the PHA copolymer. For example, the content of the PHA monomer may be 1 mol% or more, 2 mol% or more, 3 mol% or more, 5 mol% or more, or 10 mol% or more, and 99 mol% or less, 95 mol% or less, 90 mol% or less, 85 mol% or less, 80 mol% or less, 75 mol% or less, 70 mol% or less, 65 mol% or less, or 60 mol% or less, based on the total moles of monomers used in the PHA copolymer. For example, the content of the PHA monomer can be 1 mol% to 99 mol%, 1 mol% to 95 mol%, 1 mol% to 90 mol%, 1 mol% to 89 mol%, 1 mol% to 85 mol%, 1 mol% to 80 mol%, 1 mol% to 79 mol%, 1 mol% to 75 mol%, 1 mol% to 70 mol%, 1 mol% to 65 mol%, 1 mol% to 60 mol%, 0.1 mol% to 55 mol%, 0.5 mol% to 60 mol%, 0.5 mol% to 55 mol%, 1 mol% to 60 mol%, 1 mol% to 55 mol%, 1 mol% to 50 mol%, 2 mol% to 55 mol%, 3 mol% to 55 mol%, 3 mol% to 50 mol%, 5 mol% to 55 mol%, 5 mol% to 50 mol%, 10 mol% to 55 mol%, 1 ... % to 55 mol%, 10 mol% to 50 mol%, 15 mol% to 60 mol%, 15 mol% to 55 mol%, 15 mol% to 50 mol%, 20 mol% to 60 mol%, 20 mol% to 55 mol%, 20 mol% to 50 mol%, 25 mol% to 60 mol%, 25 mol% to 55 mol%, 25 mol% to 50 mol%, 25 mol% to 45 mol%, 25 mol% to 40 mol%, 30 mol% to 60 mol%, 30 mol% to 55 mol%, 30 mol% to 50 mol%, 30 mol% to 45 mol%, 30 mol% to 40 mol%, 35 mol% to 60 mol%, 35 mol% to 55 mol%, 35 mol% to 50 mol%, 40 mol% to 60 mol%, 40 mol% to 55 mol%, or 45 mol% to 55 mol%.

[0073] In addition, the PHA includes at least one 4-HB monomer, and the content of the 4-HB monomer can be controlled to adjust the crystallinity of the PHA. That is, the PHA can be a PHA copolymer with controllable crystallinity.

[0074] The crystallinity-adjusted PHA may be a PHA in which its crystallinity and amorphousness are adjusted as irregularities in its molecular structure increase. Specifically, the type and ratio of monomers or the type and / or content of isomers may be adjusted.

[0075] Meanwhile, the PHA may have a glass transition temperature (Tg) of, for example, -45°C to 80°C, -35°C to 80°C, -30°C to 80°C, -25°C to 75°C, -20°C to 70°C, -35°C to 5°C, -25°C to 5°C, -35°C to 0°C, -25°C to 0°C, -30°C to -10°C, -35°C to -15°C, -35°C to -20°C, -30°C to -20°C, -20°C to 0°C, -15°C to 0°C, or -15°C to -5°C.

[0076] For example, the crystallization temperature (Tc) of a PHA may not be measurable, or may be, for example, 60-120°C, 70-120°C, 75-120°C, 75-115°C, 75-110°C, or 90-110°C.

[0077] For example, the melting temperature (Tm) of a PHA may not be measurable, or may be, for example, 100°C to 170°C, such as 110°C to 150°C, or such as 120°C to 140°C.

[0078] The PHA may have a weight average molecular weight (Mw) of, for example, 10,000 g / mole to 1,200,000 g / mole. For example, the weight average molecular weight of the PHA may be 50,000 g / mole to 1,200,000 g / mole, 100,000 g / mole to 1,200,000 g / mole, 50,000 g / mole to 1,000,000 g / mole, 100,000 g / mole to 1,000,000 g / mole, 200,000 g / mole to 1,200,000 g / mole, 250,000 g / mole to 1,150,000 g / mole, 300,000 g / mole to 1,100,000 g / mole, 350,000 g / mole to 1,000,000 g / mole, 350,000 g / mole to 950,000 g / mole, 100,000 g / mole to 900,000 g / mole, 200,000 g / mole to 800,000 g / mole, 200,000 g / mole to 700,000 g / mole, 250,000 g / mole to 650,000 g / mole, 200,000 g / mole to 400,000 g / mole, 300,000 g / mole to 800,000 g / mole, 300,000 g / mole to 600 ,000 g / mole, 500,000 g / mole to 1,200,000 g / mole, 500,000 g / mole to 1,000,000 g / mole, 550,000 g / mole to 1,050,000 g / mole, 550,000 g / mole to 900,000 g / mole or 600,000 g / mole to 900,000 g / mole.

[0079] The PHA may have a melt index (MI) of 0.1 g / 10 min or more, 0.5 g / 10 min or more, 1 g / 10 min or more, or 2 g / 10 min or more, and 500 g / 10 min or less, 450 g / 10 min or less, 400 g / 10 min or less, 350 g / 10 min or less, 300 g / 10 min or less, 200 g / 10 min or less, 100 g / 10 min or less, 80 g / 10 min or less, 50 g / 10 min or less, 30 g / 10 min or less, 20 g / 10 min or less, 10 g / 10 min or less, or 5 g / 10 min or less, when measured according to ASTM D1238 at a temperature of 165° C. and a load of 5.0 kg. Specifically, the melt index may be 0.1 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 400 g / 10 min, 1 g / 10 min to 500 g / 10 min, 10 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 300 g / 10 min, 300 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 100 g / 10 min, 100 g / 10 min to 200 g / 10 min, 200 g / 10 min to 300 g / 10 min, 300 g / 10 min to 400 g / 10 min, 400 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 80 g / 10 min, 0.1g / 10min to 50g / 10min, 0.1g / 10min to 30g / 10min, 0.1g / 10min to 20g / 10min, 0.1g / 10min to 10g / 10min, 1g / 10min to 30g / 10min, 1g / 10min to 20g / 10min, 1g / 10min to 10g / 10min, 0.1g / 10min to 2g / 10min, 2g / 10min to 5g / 10min, 5g / 10min to 8g / 10min, 8g / 10min to 12g / 10min, 12g / 10min to 16g / 10min, 16g / 10min to 20g / 10min or 20g / 10min to 30g / 10min.

[0080] For example, the polyhydroxyalkanoate (PHA) may have a glass transition temperature (Tg) of -45 to 80°C and a melt index (MI) of 0.1 to 500 g / 10 min, the melt index being measured at a temperature of 165°C and a load of 5.0 kg according to ASTM D1238.

[0081] Meanwhile, PHA may include a combination of two or more PHAs having different crystallinity. That is, by mixing two or more PHAs having different crystallinity, PHA may be adjusted to have a content of 4-HB monomer within a specific range.

[0082] Specifically, the PHA may include a first PHA resin, a second PHA resin, or a mixed resin of the first PHA resin and the second PHA resin.

[0083] The first PHA resin and the second PHA resin may be distinguished according to the content of 4-HB monomer, glass transition temperature (Tg), crystallization temperature (Tc), and melting temperature (Tm).

[0084] Specifically, the first PHA resin may contain the 4-HB monomer in an amount of, for example, 15 to 60 mol%, 15 to 55 mol%, 20 to 55 mol%, 25 to 55 mol%, 30 to 55 mol%, 35 to 55 mol%, 20 to 50 mol%, 25 to 50 mol%, 30 to 50 mol%, 35 to 50 mol%, or 20 to 40 mol%, based on the total moles of monomers used in the first PHA resin.

[0085] The glass transition temperature (Tg) of the first PHA resin may be, for example, -45°C to -10°C, -35°C to -10°C, -35°C to -15°C, -35°C to -20°C, or -30°C to -20°C.

[0086] For example, the crystallization temperature (Tc) of the first PHA resin may not be measurable, or may be, for example, 60°C to 120°C, 60°C to 110°C, 70°C to 120°C, or 75°C to 115°C.

[0087] For example, the melting temperature (Tm) of the first PHA resin may not be measurable, or may be, for example, 100°C to 170°C, 100°C to 160°C, 110°C to 160°C, or 120°C to 150°C.

[0088] The first PHA resin may have a weight average molecular weight (Mw), for example, of 10,000 g / mole to 1,200,000 g / mole, 10,000 g / mole to 1,000,000 g / mole, 50,000 g / mole to 1,000,000 g / mole, 50,000 g / mole to 1,200,000 g / mole, 200,000 g / mole to 1,200,000 g / mole, 300,000 g / mole to 1,000,000 g / mole, 100,000 g / mole to 900,000 g / mole, 500,000 g / mole to 900,000 g / mole, 200,000 g / mole to 800,000 g / mole, or 200,000 g / mole to 400,000 g / mole.

[0089] The first PHA resin may have a melt index (MI) of 0.1 g / 10 min or more, 0.5 g / 10 min or more, 1 g / 10 min or more, or 2 g / 10 min or more, and 500 g / 10 min or less, 450 g / 10 min or less, 400 g / 10 min or less, 350 g / 10 min or less, 300 g / 10 min or less, 200 g / 10 min or less, 100 g / 10 min or less, 80 g / 10 min or less, 50 g / 10 min or less, 30 g / 10 min or less, 20 g / 10 min or less, 10 g / 10 min or less, or 5 g / 10 min or less, when measured according to ASTM D1238 at a temperature of 165° C. and a load of 5.0 kg. Specifically, the melt index may be 0.1 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 400 g / 10 min, 1 g / 10 min to 500 g / 10 min, 10 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 300 g / 10 min, 300 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 100 g / 10 min, 100 g / 10 min to 200 g / 10 min, 200 g / 10 min to 300 g / 10 min, 300 g / 10 min to 400 g / 10 min, 400 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 80 g / 10 min, 0.1g / 10min to 50g / 10min, 0.1g / 10min to 30g / 10min, 0.1g / 10min to 20g / 10min, 0.1g / 10min to 10g / 10min, 1g / 10min to 30g / 10min, 1g / 10min to 20g / 10min, 1g / 10min to 10g / 10min, 0.1g / 10min to 2g / 10min, 2g / 10min to 5g / 10min, 5g / 10min to 8g / 10min, 8g / 10min to 12g / 10min, 12g / 10min to 16g / 10min, 16g / 10min to 20g / 10min or 20g / 10min to 30g / 10min.

[0090] Meanwhile, the second PHA resin may include 4-HB monomer in an amount of 0.1 mol% to 30 mol% based on the total moles of monomers used in the second PHA resin. For example, the second PHA may include 4-HB monomer in an amount of 0.1 mol% to 30 mol%, 0.5 mol% to 30 mol%, 1 mol% to 30 mol%, 3 mol% to 30 mol%, 1 mol% to 28 mol%, 1 mol% to 25 mol%, 1 mol% to 24 mol%, 1 mol% to 20 mol%, 1 mol% to 15 mol%, 2 mol% to 25 mol%, 3 mol% to 25 mol%, 3 mol% to 24 mol%, 5 mol% to 24 mol%, 5 mol% to 20 mol%, greater than 5 mol% to less than 20 mol%, 7 mol% to 20 mol%, 10 mol% to 20 mol%, 15 mol% to 25 mol%, or 15 mol% to 24 mol%, based on the total moles of monomers used in the second PHA resin.

[0091] The first PHA resin and the second PHA resin may be different from each other in terms of the content of the 4-HB monomer.

[0092] The glass transition temperature (Tg) of the second PHA resin may be, for example, -30°C to 80°C, for example, -30°C to 10°C, for example, -25°C to 5°C, for example, -25°C to 0°C, for example, -20°C to 0°C, or for example, -15°C to 0°C.

[0093] The glass transition temperature (Tg) of the first PHA resin and the glass transition temperature (Tg) of the second PHA resin may be different from each other.

[0094] The second PHA resin may have a crystallization temperature (Tc) of, for example, 70°C to 120°C, such as 75°C to 115°C or 80°C to 110°C, or may be unmeasurable, for example.

[0095] The second PHA resin may have a melting temperature (Tm) of, for example, 100°C to 170°C, for example, 105°C to 165°C, for example, 110°C to 160°C, for example, 100°C to 150°C, for example, 115°C to 155°C, for example, 120°C to 160°C, or for example, 120°C to 150°C.

[0096] The second PHA resin may have a weight average molecular weight (Mw) of 10,000 g / mole to 1,200,000 g / mole, 50,000 g / mole to 1,100,000 g / mole, 1,00,000 g / mole to 1,000,000 g / mole, 300,000 g / mole to 1,000,000 g / mole, 100,000 g / mole to 900,000 g / mole, 200,000 g / mole to 800,000 g / mole, 200,000 g / mole to 600,000 g / mole, 200,000 g / mole to 400,000 g / mole, or 400,000 g / mole to 700,000 g / mole.

[0097] Specifically, the first PHA resin has a glass transition temperature (Tg) of -35°C to -15°C, the second PHA resin satisfies at least one property selected from the following: a glass transition temperature (Tg) of -15°C to 0°C, a crystallization temperature (Tc) of 80°C to 110°C, and a melting temperature (Tm) of 120°C to 160°C, and the glass transition temperature (Tg) of the first PHA resin and the glass transition temperature (Tg) of the second PHA resin may be different from each other. In addition, the crystallization temperature (Tc) and the melting temperature (Tm) of the first PHA resin may not be measured.

[0098] The second PHA resin may have a melt index (MI) of 0.1 g / 10 min or more, 0.5 g / 10 min or more, 1 g / 10 min or more, or 2 g / 10 min or more, and 500 g / 10 min or less, 450 g / 10 min or less, 400 g / 10 min or less, 350 g / 10 min or less, 300 g / 10 min or less, 200 g / 10 min or less, 100 g / 10 min or less, 80 g / 10 min or less, 50 g / 10 min or less, 30 g / 10 min or less, 20 g / 10 min or less, 10 g / 10 min or less, or 5 g / 10 min or less, when measured according to ASTM D1238 at a temperature of 165° C. and a load of 5.0 kg. Specifically, the melt index may be 0.1 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 400 g / 10 min, 1 g / 10 min to 500 g / 10 min, 10 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 300 g / 10 min, 300 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 100 g / 10 min, 100 g / 10 min to 200 g / 10 min, 200 g / 10 min to 300 g / 10 min, 300 g / 10 min to 400 g / 10 min, 400 g / 10 min to 500 g / 10 min, 0.1 g / 10 min to 80 g / 10 min, 0.1g / 10min to 50g / 10min, 0.1g / 10min to 30g / 10min, 0.1g / 10min to 20g / 10min, 0.1g / 10min to 10g / 10min, 1g / 10min to 30g / 10min, 1g / 10min to 20g / 10min, 1g / 10min to 10g / 10min, 0.1g / 10min to 2g / 10min, 2g / 10min to 5g / 10min, 5g / 10min to 8g / 10min, 8g / 10min to 12g / 10min, 12g / 10min to 16g / 10min, 16g / 10min to 20g / 10min or 20g / 10min to 30g / 10min.

[0099] The melt index (MI) of the first PHA resin and the melt index (MI) of the second PHA resin may be different from each other.

[0100] When the first PHA resin and the second PHA resin each satisfy at least one of the 4-HB monomer content, glass transition temperature (Tg), crystallization temperature (Tc), melting temperature (Tm) and melt index (MI) within the above ranges, it may be more conducive to achieving the desired effects in the present disclosure.

[0101] In addition, the first PHA resin and the second PHA resin may each be a PHA whose crystallinity is controllable.

[0102] For example, the first PHA resin may include an amorphous PHA resin (hereinafter referred to as an aPHA resin), and the second PHA resin may include a semi-crystalline PHA resin (hereinafter referred to as a scPHA resin).

[0103] Specifically, the first PHA resin may be an aPHA resin or a mixed resin of an aPHA resin and a scPHA resin.

[0104] Specifically, the second PHA resin may be a scPHA resin or a mixed resin of an aPHA resin and a scPHA resin.

[0105] aPHA resins and scPHA resins can be distinguished based on the content of 4-HB monomer, glass transition temperature (Tg), crystallization temperature (Tc), melting temperature (Tm), melt index (MI), etc.

[0106] The aPHA resin may include 4-HB monomer in an amount of, for example, 25 mol % to 50 mol % based on the total moles of monomers used in the PHA resin.

[0107] The aPHA resin may have a glass transition temperature (Tg), for example, of -35°C to -20°C.

[0108] The crystallization temperature (Tc) of aPHA resins may not be measured.

[0109] The melting temperature (Tm) of aPHA resins may not be measured.

[0110] The scPHA resin can include 4-HB monomer in an amount of, for example, 1 mol % to less than 25 mol % based on the total moles of monomers used in the PHA resin.

[0111] The scPHA resin may have a glass transition temperature (Tg) of -20°C to 0°C.

[0112] The scPHA resin may have a crystallization temperature (Tc) of 75°C to 115°C.

[0113] The scPHA resin may have a melting temperature (Tm) of 110°C to 160°C.

[0114] According to an embodiment of the present disclosure, the amount of the binder may be 0.1 wt % or more, 0.2 wt % or more, 0.3 wt % or more, 0.4 wt % or more, 0.5 wt % or more, 1 wt % or more, 2 wt % or more, 3 wt % or more or 5 wt % or more, and 20 wt % or less, 18 wt % or less, 17 wt % or less, 16 wt % or less, 15 wt % or less, 10 wt % or less, 8 wt % or less, 7 wt % or less, 6 wt % or less or 5 wt % or less, based on the total weight of the electrode active material composition.

[0115] Specifically, the electrode active material composition may contain the binder in an amount of 0.1 wt % to 20 wt %, 0.2 wt % to 18 wt %, 0.5 wt % to 15 wt %, 1 wt % to 15 wt %, 3 wt % to 15 wt %, 5 wt % to 15 wt %, or 5 wt % to 10 wt %, based on the total weight of the electrode active material composition.

[0116] If the content of the binder is below the above range, the effect of using the binder may not be obvious. If the content of the binder exceeds the above range, as the content of the binder increases, the unit volume capacity of the secondary battery will decrease due to the relative decrease in the content of the electrode active material.

[0117] According to another embodiment of the present disclosure, when the PHA includes a mixed resin of a first PHA resin and a second PHA resin, a weight ratio of the first PHA resin to the second PHA resin may be, for example, 1:(0.5 to 3), for example, 1:(0.5 to 2.5), or for example, 1:(0.5 to 2).

[0118] According to another embodiment of the present disclosure, the weight ratio of the electrode active material, the binder and the conductive material can be (4.0 to 9.8):(0.1 to 3.0):(0.1 to 3.0), (6.0 to 9.6):(0.2 to 2.0):(0.2 to 2.0), (6.0 to 9.0):(0.5 to 2.0):(0.5 to 2.0) or (7.0 to 9.0):(0.5 to 1.5):(0.5 to 1.5).

[0119] In the electrode active material composition, when the content of the binder and the weight ratio of the electrode active material, the binder and the conductive material satisfy the above ranges, the bonding strength and performance of the secondary battery can be effectively improved while reducing the use of the binder.

[0120] In addition, the electrode active material composition may further include various commonly used binders, such as poly(vinylidene fluoride - hexafluoropropylene) (PVdF - co - HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate, styrene - butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyvinyl alcohol (PVA), and polyvinyl acetate.

[0121] When PHA is mixed with various types of commonly used binders, as long as the desired effects in the present disclosure are not impaired, there is no specific limitation on the mixing ratio.

[0122] In addition, the binder can be used in the negative electrode active material composition applied to the negative electrode, the positive electrode active material composition applied to the positive electrode, or both. For example, the binder can be used in the negative electrode active material composition to effectively achieve the desired effects in the present disclosure.

[0123] Electrode active materials

[0124] The electrode active material composition according to an embodiment of the present disclosure may include an electrode active material.

[0125] The electrode active material may include a negative electrode active material, a positive electrode active material, or both. Specifically, the electrode active material may be a negative electrode active material.

[0126] There is no specific limitation on the negative electrode active material as long as it is a material capable of reversibly inserting or extracting lithium (Li + ).

[0127] The negative electrode active material may include, for example, at least one selected from the group consisting of a carbon - based negative electrode active material, a silicon - based negative electrode active material, lithium metal, and a lithium alloy.

[0128] The carbon - based negative electrode active material may include low - crystalline carbon, high - crystalline carbon, or a mixture thereof. The low - crystalline carbon may include soft carbon, hard carbon, or a mixture thereof. The high - crystalline carbon may include at least one of the following high - temperature calcined carbons selected from the group consisting of natural graphite, kish graphite, pyrolytic carbon, mesophase pitch - based carbon fiber, meso - carbon microbeads, mesophase pitch, and coke derived from petroleum or coal tar pitch.

[0129] The silicon - based negative electrode active material may include, for example, at least one selected from the group consisting of Si, silicon oxide particles (SiO x , 0 < x ≤ 2), Si - metal alloys, and alloys of Si and silicon oxide particles (SiO x , 0 < x ≤ 2). The silicon oxide particles (SiO x , 0 < x ≤ 2) may be composed of crystalline SiO2 A composite composed of and amorphous Si.

[0130] The lithium metal may be in the form of a lithium metal film or a lithium metal powder.

[0131] The lithium alloy can be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al) and tin (Sn).

[0132] Meanwhile, examples of positive electrode active materials include layered compounds or compounds substituted with one or more transition metals, such as lithium cobalt oxide (LiCoO 2 ); Lithium nickel oxide (LiNiO 2 ); Li[Ni a Co b Mn c M 1 d ]O 2 (In this formula, M 1 is an element selected from the group consisting of Al, Ga and In, or two or more of these elements, 0.3≤a<1.0, 0≤b≤0.5, 0≤c≤0.5, 0≤d≤0.1, and a+b+c+d=1); Li (Li e M 2 f-e-f' M 3 f' ) 2-g A g (In this formula, 0≤e≤0.2, 0.6≤f≤1, 0≤f'≤0.2, 0≤g≤0.2, M 2 The invention comprises Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn and Ti, wherein M 3 is at least one selected from the group consisting of Al, Mg and B, and A is at least one selected from the group consisting of P, F, S and N); Li 1+h Mn 2-h O 4 (in this formula, 0≤h≤0.33), lithium manganese oxide, such as LiMnO 3 、LiMn 2 O 3 and LiMnO 2 ; Lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides, such as LiV 3 O 8 、V 2 O5 , Cu 2 V 2 O 7 ; LiNi 1-i M 4 i O 2 The Ni-type lithium nickel oxide represented by 4 is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and 0.01≤i≤0.3); by the formula LiMn 2-j M 5 j O 2 (In this formula, M 5 is Co, Ni, Fe, Cr, Zn or Ta, and 0.01≤j≤0.1) or Li 2 Mn 3 M 6 O 8 (In this formula, M 6 is a lithium manganese composite oxide represented by Fe, Co, Ni, Cu or Zn; LiMn 2 O 4 , wherein some of the Li in the formula is replaced by alkaline earth metal ions; disulfide compounds; LiFe 3 O 4 ; and Fe 2 (MoO 4 ) 3 , but not limited to this.

[0133] The amount of the electrode active material used can be 40 weight % or more, 50 weight % or more, 60 weight % or more, 65 weight % or more, 70 weight % or more, 75 weight % or more or 80 weight % or more, and 98 weight % or less, 95 weight % or less, 90 weight % or less, 88 weight % or less or 85 weight % or less, based on the total weight of the electrode active material composition.

[0134] Conductive Materials

[0135] The electrode active material composition according to an embodiment of the present disclosure may include a conductive material.

[0136] The conductive material is intended to enhance conductivity. The conductive material is not particularly limited as long as it is an electron conductive material that does not cause chemical changes in the secondary battery.

[0137] For example, the conductive material may be graphite, such as natural graphite and synthetic graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and Super P; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbons, aluminum, and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; or conductive metal oxides, such as titanium oxide. Specifically, the conductive material may include carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and Super P.

[0138] The amount of the conductive material may be 1 wt % or more, 2 wt % or more, 3 wt % or more, 5 wt % or more or 10 wt % or more, and 30 wt % or less, 25 wt % or less or 20 wt % or less, based on the total weight of the electrode active material composition.

[0139] additive

[0140] The electrode active material composition according to an embodiment of the present disclosure may include additives in addition to the electrode active material, the binder, and the conductive material.

[0141] The additives may include, for example, viscosity modifiers, fillers, dispersants, or combinations thereof.

[0142] The viscosity modifier may be carboxymethyl cellulose, polyacrylic acid, etc. The viscosity may be adjusted by adding the viscosity modifier to facilitate the coating process on the electrode current collector.

[0143] The filler is an auxiliary component that suppresses electrode expansion. The filler is not specifically limited as long as it is a fiber material that does not cause chemical changes in the secondary battery. For example, the filler can be a fiber material such as an olefin polymer (such as polyethylene and polypropylene), glass fiber or carbon fiber, etc.

[0144] The dispersant may include an aqueous dispersant or an organic dispersant, such as N-methyl-2-pyrrolidone.

[0145] [electrode]

[0146] According to an embodiment of the present disclosure, there is provided an electrode including an electrode active material composition.

[0147] Specifically, the electrode includes an electrode active material, a binder, and a conductive material, wherein the binder may include polyhydroxyalkanoate (PHA).

[0148] For example, the electrode may be manufactured by mixing the electrode active material composition with a solvent to prepare an electrode slurry (negative electrode slurry or positive electrode slurry), applying the electrode slurry to an electrode (negative electrode or positive electrode) collector, drying it, and then pressing it.

[0149] The solvent contained in the electrode slurry can be an organic solvent, such as N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), acetone and dimethylacetamide, or water. These solvents can be used alone or in combination of two or more. Considering the coating thickness and manufacturing yield of the slurry, the amount of the solvent used is sufficient to dissolve and disperse the electrode active material, the binder and the conductive material.

[0150] The electrodes may comprise a negative electrode, a positive electrode, or both.

[0151] The negative electrode can be manufactured by conventional methods known in the art. For example, the negative electrode can be manufactured by preparing a negative electrode slurry containing an electrode active material composition (negative electrode active material composition) and a solvent, applying the negative electrode slurry to a negative electrode current collector, drying it, and then pressing it.

[0152] The negative electrode current collector for the negative electrode may have a thickness of 3 μm to 500 μm. The negative electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the secondary battery. For example, copper, gold, stainless steel, aluminum, nickel, titanium, sintered carbon, or copper or stainless steel surface-treated with carbon, nickel, titanium or silver, or aluminum-cadmium alloy may be used. In addition, the bonding strength of the negative electrode active material may be enhanced by forming fine irregularities on the surface. The negative electrode current collector may be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and nonwovens.

[0153] The positive electrode can be manufactured by conventional methods known in the art. For example, the positive electrode can be manufactured by preparing a positive electrode slurry containing an electrode active material composition (positive electrode active material composition) and a solvent, applying (coating) the positive electrode slurry to a current collector of a metal material, pressing it, and then drying it.

[0154] The current collector of the metal material is a highly conductive metal to which the positive electrode slurry can be easily adhered, and as long as the current collector has high conductivity within the voltage range of the secondary battery without causing chemical changes in the secondary battery, there is no specific restriction. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium or silver can be used. In addition, the bonding strength of the positive electrode active material can be enhanced by forming fine irregularities on the surface of the current collector. The current collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and nonwovens. The current collector can have a thickness of 3 μm to 500 μm.

[0155] [Secondary battery]

[0156] According to an embodiment of the present disclosure, there is provided a secondary battery including a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte, wherein at least one of the negative electrode and the positive electrode includes a binder including polyhydroxyalkanoate (PHA).

[0157] The separator is used to physically separate the two electrodes in the secondary battery of the present disclosure. The separator commonly used in lithium secondary batteries can be used without any specific restrictions. In particular, it is desirable to have low resistance to the movement of electrolyte ions and excellent electrolyte wetting ability.

[0158] The separator may be formed of a porous substrate. Any porous substrate commonly used in electrochemical devices may be used as the porous substrate. For example, a polyolefin porous film or nonwoven fabric may be used, but is not particularly limited thereto.

[0159] Examples of the polyolefin porous film include films formed using polyolefin polymers such as polyethylene, such as high-density polyethylene, linear low-density polyethylene, low-density polyethylene, and ultra-high molecular weight polyethylene, polypropylene, polybutene, and polypentene, alone or as a mixture thereof.

[0160] Examples of the nonwoven fabric include nonwoven fabrics formed of polymers such as polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, and polyethylene naphthalate, alone or as a mixture thereof, in addition to the polyolefin nonwoven fabric. The nonwoven fabric may have a structure of a spunbond nonwoven fabric or a meltblown nonwoven fabric composed of long fibers.

[0161] The thickness of the porous substrate is not particularly limited, but it may be 1 to 100 μm or 5 to 50 μm.

[0162] The size and porosity of the pores present in the porous substrate are also not particularly limited. For example, the pores present in the porous substrate may have a size of 0.001 to 50 μm and a porosity of 10 to 95%.

[0163] Meanwhile, the electrolyte may include a lithium salt.

[0164] Lithium salts can act as lithium ions (Li + ) moving channel.

[0165] The lithium salt is not particularly limited in the present disclosure, and any lithium salt commonly used in electrolytes of secondary batteries may be used without limitation.

[0166] Specifically, the lithium salt may include at least one selected from the group consisting of: LiPF 6、LiAsF 6 、LiFSI、LiTFSI、LiCF 3 SO 3 、LiN(CF 3 SO 2 ) 2 , LiBF 4 , LiBF 6 、LiSbF 6 、LiN(C 2 F 5 SO 2 ) 2 and LiSO 3 CF 3 More specifically, the lithium salt may include a selected from the group consisting of LiPF 6 、LiAsF 6 , LiFSI, LiTFSI and LiBF 4 At least one of the groups consisting of.

[0167] Furthermore, the electrolyte may contain an organic solvent.

[0168] Organic solvents commonly used in the electrolyte of secondary batteries can be used without restriction. As a representative, any one or a mixture of two or more selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methylpropyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, cyclopentane sulfone, gamma-butyrolactone, propylene sulfite and tetrahydrofuran can be used.

[0169] Specifically, the organic solvent may include at least one selected from the group consisting of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC).

[0170] In addition, the electrolyte may further contain additives such as an overcharge protector contained in a conventional electrolyte.

[0171] The secondary battery according to the present disclosure may be manufactured by laminating (stacking) and folding a separator and an electrode, in addition to a common winding method.

[0172] The shape of the secondary battery is not particularly limited and may include various shapes such as a cylindrical shape, a laminated shape, and a button shape.

[0173] When the secondary battery according to an embodiment of the present disclosure is charged at a constant current of 0.05C until the voltage reaches 3V, and then discharged at a constant current of 0.05C until the voltage reaches 0.01V, the coulombic efficiency represented by the following equation 1 can be, for example, 90% or higher, for example, 92% or higher, for example, 93% or higher, for example, 94% or higher, or for example, 95% or higher.

[0174] [Equation 1]

[0175] Coulomb efficiency (%) = discharge capacity / charge capacity × 100

[0176] In addition, when measured after repeating the above charging and discharging process twice, the secondary battery according to the embodiment of the present disclosure may have 250 mAhg -1 or larger, 270mAhg -1 or larger, 280mAhg -1 or larger, 285mAhg -1 or larger, 290mAhg -1 or larger, 295mAhg -1 or larger, 300mAhg -1 or larger, 310mAhg -1 or larger, 320mAhg -1 or larger or 330mAhg -1 or greater specific capacity.

[0177] The secondary battery according to the embodiment of the present disclosure has low resistance even when repeatedly cycled due to the strong bonding force of the binder, can maintain high capacity cycling for a long time even when the amount of the binder is reduced, and can maintain excellent structural stability even after long-term cycling.

[0178] In addition, the secondary battery according to the embodiment of the present disclosure has flame retardant properties that do not spread combustion and do not generate harmful substances when incinerated by using polyhydroxyalkanoate (PHA) as a binder.

[0179] Therefore, the secondary battery according to the present disclosure may be used not only in a battery cell used as a power source for small devices but also may be advantageously used in a unit battery of a medium to large-sized battery module including a plurality of battery cells.

[0180] The battery module can be used as a power source for medium- and large-sized devices requiring high-temperature stability, long cycle characteristics, and high-capacity characteristics.

[0181] Examples of medium and large devices include, but are not limited to, power tools driven by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.

[0182] Embodiments of the present invention

[0183] Hereinafter, the present disclosure will be described in detail with reference to examples. However, the following examples are intended to illustrate the present disclosure, and the scope of the present disclosure is not limited thereto.

[0184] Example 1

[0185] <Preparation of negative electrode>

[0186] Preparation of negative electrode active material composition and negative electrode slurry

[0187] Graphite as a negative electrode active material, PHA (3-HB-co-4-HB, aPHA) (manufacturer: CJ) as a binder, and ultra black as a conductive material were mixed in a weight ratio of 8:1:1 to prepare a negative electrode active material composition.

[0188] 80 mg of the negative electrode active material composition was added to 0.5 ml of N-methyl-2-pyrrolidone (NMP) as a solvent to prepare a negative electrode slurry.

[0189] Preparation of negative electrode

[0190] The negative electrode slurry was coated onto a 20 μm copper foil with a thickness of 15 μm, and then dried in a vacuum oven at 100° C. for 12 hours and rolled to manufacture a negative electrode.

[0191] <Preparation of positive electrode>

[0192] Preparation of positive electrode active material composition and positive electrode slurry

[0193] LiCoO as the positive electrode active material 2 , polyvinylidene fluoride (PVdF) as a binder, and carbon black as a conductive material were mixed in a weight ratio of 8:1:1 to prepare a positive electrode active material composition.

[0194] 80 mg of the positive electrode active material composition was added to 0.5 ml of N-methyl-2-pyrrolidone (NMP) as a solvent to prepare a positive electrode slurry.

[0195] Preparation of positive electrode

[0196] The positive electrode slurry was coated on an 18 μm aluminum (Al) foil with a thickness of 15 μm, and then dried in a vacuum oven at 100° C. for 12 hours and rolled to manufacture a positive electrode.

[0197] <Manufacturing of lithium secondary batteries>

[0198] The negative electrode prepared above was punched into a 1.2 cm 2 The positive electrode prepared above was punched into a surface area of ​​1.2 cm 2 surface area to make button batteries.

[0199] LiPF 6 The electrolyte was prepared by dissolving in a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) at a concentration of 1 M.

[0200] Thereafter, the button cell was sealed using a crimper and then subjected to a constant voltage charging step of charging at a constant current of about 0.05C and maintaining the voltage until it reached about 1 / 6 of the current.

[0201] Example 2

[0202] A negative electrode active material composition, a negative electrode, a positive electrode and a lithium secondary battery were manufactured using the same method as in Example 1, except that graphite as a negative electrode active material, PHA (3-HB-co-4-HB, aPHA) (manufacturer: CJ) as a binder and ultra black as a conductive material were mixed in a weight ratio of 8.5:0.5:1.

[0203] Comparative Example 1

[0204] A negative electrode active material composition, a negative electrode, a positive electrode, and a lithium secondary battery were manufactured using the same method as in Example 1, except that polyvinylidene fluoride (PVdF) was used as a binder when preparing the negative electrode active material composition.

[0205] Evaluation Example

[0206] Evaluation Example 1: Solubility Evaluation

[0207] 10 mg of PVdF (powder) and 10 mg of aPHA (pellets) used as binders in Comparative Example 1 and Example 1 were added to a 1:1 (volume ratio) mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) and left for 1 day. The solubility of each binder was observed at the beginning of the addition and 1 day after the addition. The results are shown in FIG. Figure 1 shown.

[0208] from Figure 1It can be seen that, for the PVdF used in Comparative Example 1, the PVdF (powder) was initially mixed with the mixed solvent, but after 1 day, the PVdF (powder) was separated from the mixed solvent and formed a layer. For the aPHA (pellets) used in Example 1, it was not initially dissolved in the mixed solvent even after 1 day of addition, but remained as aPHA (pellets).

[0209] Evaluation Example 2: Antioxidant Evaluation

[0210] The oxidation resistance was evaluated using cyclic voltammetry (WBCS3000, Wonatech, Korea) under half-cell conditions. Figure 2 shown.

[0211] Specifically, Figure 2 (a) shows the voltage-current curves of the electrodes of Comparative Example 1 and Example 1. Figure 2 (b) shows the voltage-current curves of the polyvinylidene fluoride (PVdF) binder used in Comparative Example 1 and the PHA (3-HB-co-4-HB, aPHA) binder used in Example 1.

[0212] from Figure 2 As can be seen in FIG. 1 , in the electrode of Example 1 using aPHA as a binder, the oxidation resistance is excellent and is electrochemically stable at a level similar to that of the electrode of Comparative Example 1 using PVdF as a binder.

[0213] Evaluation Example 3: Electrochemical Property Evaluation

[0214] The electrochemical characteristics of the secondary batteries of Examples 1 and 2 and Comparative Example 1 were each evaluated.

[0215] (1) Specific capacity

[0216] The secondary batteries manufactured in Examples and Comparative Examples were each charged at a constant current of 0.05 C until the voltage reached 3 V, and then discharged at a constant current of 0.05 C until the voltage reached 0.01 V, and the specific capacity of constant current charging and discharging was measured.

[0217] (2) Coulomb efficiency

[0218] The secondary batteries manufactured in the examples and comparative examples were each charged at a constant current of 0.05 C until the voltage reached 3 V and then discharged at a constant current of 0.05 C until the voltage reached 0.01 V, and the coulombic efficiency represented by the following Equation 1 was calculated.

[0219] [Equation 1]

[0220] Coulomb efficiency (%) = discharge capacity / charge capacity × 100

[0221] Figures 3 to 5 is a graph showing the results of measuring the specific capacity and coulombic efficiency of the secondary batteries of Example 1, Example 2, and Comparative Example 1. The results are summarized in Table 1 below.

[0222] [Table 1]

[0223]

[0224] like Figures 3 to 5 As shown in Table 1, in the secondary batteries of Examples 1 and 2 using aPHA as a binder, both the specific capacity and the coulombic efficiency were improved compared to the secondary battery of Comparative Example 1 using PVdF as a binder.

[0225] In addition, when comparing the specific capacity and coulombic efficiency of the secondary batteries of Example 1 and Example 2 with controllable binder content, in the secondary battery of Example 2, in which the binder content is reduced to a weight ratio of the negative electrode active material, the binder and the conductive material of 8.5:0.5:1, even if a smaller amount of binder is used, its specific capacity is further improved and the coulombic efficiency is maintained at a similar level to the secondary battery of Example 1 (in which the weight ratio of the negative electrode active material, the binder and the conductive material is 8:1:1).

[0226] at the same time, Figure 6 and Figure 7 is a graph showing the results of measuring the impedance of the secondary batteries of Example 1 and Comparative Example 1 in the first cycle and the tenth cycle.

[0227] At 0.01V and 0.02Ag -1 The impedance is measured under the conditions of

[0228] from Figure 6 and Figure 7 It can be seen that, in the secondary battery of Example 1 using aPHA as a binder, the resistance is reduced even when cycles are repeated due to excellent bonding strength, compared with the secondary battery of Comparative Example 1 using PVdF as a binder.

[0229] also, Figure 8 : is a graph showing the results of measuring the specific capacity and coulombic efficiency of the secondary battery of Example 2 according to the number of cycles (0 to 70).

[0230] from Figure 8 It can be seen that in the secondary battery of Example 2, even when the number of cycles increases, the specific capacity and the coulombic efficiency do not decrease.

Claims

1. An electrode active material composition comprising an electrode active material, a binder and a conductive material, wherein the binder comprises polyhydroxyalkanoate (PHA).

2. The electrode active material composition according to claim 1, wherein the polyhydroxyalkanoate (PHA) has a glass transition temperature (Tg) of -45°C to 80°C and a melt index (MI) of 0.1 g / 10 min to 500 g / 10 min, the melt index being measured at a temperature of 165°C and a load of 5.0 kg according to ASTM D1238.

3. The electrode active material composition according to claim 1, wherein the polyhydroxyalkanoate (PHA) comprises at least one monomer selected from the group consisting of 4-hydroxybutyrate (4-HB), 3-hydroxybutyrate (3-HB), 3-hydroxypropionate (3-HP), 3-hydroxyvalerate (3-HV), 3-hydroxyhexanoate (3-HH), 4-hydroxyvalerate (4-HV), 5-hydroxyvalerate (5-HV) and 6-hydroxyhexanoate (6-HH). 4 . The electrode active material composition according to claim 3 , wherein the polyhydroxyalkanoate (PHA) comprises a PHA homopolymer composed of 4-hydroxybutyrate (4-HB) monomers.

5. The electrode active material composition according to claim 3, wherein the polyhydroxyalkanoate (PHA) comprises a PHA copolymer containing a 4-hydroxybutyrate (4-HB) monomer, wherein the amount of the 4-hydroxybutyrate (4-HB) monomer is 1 mol % to 99 mol % based on the total moles of monomers used in the PHA copolymer. 6 . The electrode active material composition according to claim 1 , wherein the binder is used in an amount of 0.1 wt % to 20 wt % based on the total weight of the electrode active material composition.

7. The electrode active material composition according to claim 1, wherein the weight ratio of the electrode active material, the binder and the conductive material is (4.0 to 9.8):(0.1 to 3.0):(0.1 to 3.0). 8 . The electrode active material composition according to claim 1 , wherein the electrode active material is a negative electrode active material.

9. The electrode active material composition according to claim 8, wherein the negative electrode active material comprises at least one selected from the group consisting of: a carbon-based negative electrode active material, a silicon-based negative electrode active material, lithium metal and a lithium alloy, and The conductive material includes at least one selected from the group consisting of graphite, carbon black, conductive fibers, conductive tubes, metal powders, conductive whiskers, and conductive metal oxides.

10. An electrode comprising an electrode active material, a binder and a conductive material, wherein the binder comprises polyhydroxyalkanoate (PHA).

11. A secondary battery comprising a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte, wherein at least one of the negative electrode and the positive electrode comprises a binder comprising polyhydroxyalkanoate (PHA).

12. The secondary battery according to claim 11, wherein when the secondary battery is charged at a constant current of 0.05C until the voltage reaches 3V and then discharged at a constant current of 0.05C until the voltage reaches 0.01V, the coulombic efficiency represented by the following equation 1 is 93% or more, and the specific capacity measured after repeating the above charging and discharging twice is 280 mAh g -1 or higher: [Equation 1] Coulombic efficiency (%) = discharge capacity / charge capacity × 100.

Citation Information

Patent Citations

  • Multi-layer Electrode with Different Binder Content in each layer and Lithium Secondary Battery Comprising the Same

    KR102071585B1